Study guide, seven simple secrets: what the best teachers know and do - Breaux, Annette (Routledge, 2015)
"This Study Guide provides thought-provoking questions and easy-to-implement activities to help you apply the concepts in the bestselling book, Seven Simple Secrets, 2nd Edition. Step by step, it walks you through considering what you have read, taking action to implement the secrets and strategies of highly-effective teachers, and sharing your learning with others all leading to improved teaching and learning! You can work on the guide independently, in book studies, in professional learning communities (PLCs), and in professional development sessions. This guide will help you to take full advantage of the seven secrets and implement them immediately in your own classroom!"--